PROSPECTIVE EFFECT OF RED ALGAE, ACTINOTRICHIA FRAGILIS, AGAINST SOME OSTEOARTHRITIS AETIOLOGY - Sayed, Amany A.; Sadek, Shimaa A.; Soliman, Amel M.; Marzouk, Mohamed (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Osteoarthritis (OA) is a progressive disease characterized by joints pain and articular cartilage destruction. Most of the current treatment strategies for OA are effective for symptoms relief but are accompanied with adverse side effect. Thus, the present investigation aims to evaluate the potential influence of red algae, Actinotrichia fragilis, in the dry powder form (AFP) or gel form (AFG) on some relevant factors of OA progression as well as assess its safety through in vitro and in vivo experiments. Materials and Methods: In vitro, AFP was analyzed for its chemical constituents screening, amino acid, proteinase inhibitory activity, HRBC membrane stabilization activity, free radical scavenging activity, total antioxidant potency, nitric oxide radical scavenging power. In vivo, Organization for Economic Co-operation and Development (OECD) toxicity test was performed to test the safety of AFP on rats. Results: The present findings revealed that AFP and AFG can be considered as inflammatory-proteinase-oxidant inhibitor and considered to be safe according to the OECD guideline. Conclusion: AFP and AFG may have the potency to become the therapeutic candidate for OA disease as it prevents the key causes of OA initiation.